Effect of Body Condition and Supplementary Feeding on the Reproductive Performance of Awassi Ewes: A. D. Salman , Hadeel K. Ibrahim , A. F. Al-Khalisy - Salman, A. D. (The Iraqi Journal of Veterinary Medicine, 2009)
This study was conducted to evaluate the effect of body condition score (BCS) and supplementary feedingon the reproductive performance of Awassi ewes.One hundred sixty Awassi ewes aged 3-5 years (Average live weight 47.41±0.76) were used in acompletely randomized design. Six weeks before mating ewes were screened for their body conditionscore (BCS) and divided into two groups, low BCS (<2.0) and high BCS (>2.0) and ewes in each groupwere subdivided according to BCS and to non-supplemented and supplemented groups (n=40 ewes).Therefore, the four groups were:1. Group (LBCN) = Low Body Condition Non-supplemented.2. Group (LBCS) = Low Body Condition Supplemented.3. Group (HBCN) = High Body Condition Non-supplemented.4. Group (HBCS) = High Body Condition Supplemented.All ewes received ad libitum barley straw, and (350g DM/ewe/day) whole barley grains. The supplementedgroups (groups 2 and 4) were fed Mating Feed Blocks (MFB) ad libitum. Mature fertile Awassi rams(Three rams / group) were run with each group.The results showed that the pre-mating, mating, andpost-mating condition scores and body weights of the non-supplemented Ewes (Groups 1 and 3) aremaintained throughout the trial. Ewes offered supplementary feed the supplemented ewes (Groups 2and 4) gained in body condition score and weights, the differences were not significant. The BCS andweights at mating for supplemented groups are 2.12, 2.64 and 46.11, 53.38 kg for groups 2 and 4respectively. The results showed that the reproductive performance of Awassi ewes improved considerablydue initial BCS and MFB supplementation. The percent of ewes lambed after mating during the first andsecond estrus cycles were significantly (P<0.05) affected by ewes' initial BCS and MFB supplementation.The percent of ewes lambed in first cycle were 50%, 77%, 72.3% and 87% for groups LBCN, LBCS,HBCN and HBCS respectively. Supplementation of low BCS ewes resulted a significant (P<0.05)improvement in conception rate (17.5%) and lambing rate (12%). The results have not shown anysignificant of initial BCS and supplementation on twinning percentage. The percent of barren ewes at endof the trial was higher (20%, P<0.05) in LBCN compared